Pharmacokinetic Herb-Drug Interactions of Xiang-Sha-Liu-Jun-Zi-Tang and Paclitaxel in Male Sprague Dawley Rats and Its Influence on Enzyme Kinetics in Human Liver Microsomes - Kapelemera, Alinafe Magret; Uang, Yow-Shieng; Wang, Li-Hsuan; Wu, Tien-Yuan; Lee, Fang-Yu; Tai, Li; Wang, Ching-Chiung; Lee, Chia-Jung (Frontiers in Pharmacology, 2022)
Paclitaxel is a prescribed anticancer drug used to treat various cancers. It is a substrate of cytochrome P-450 (CYP-450) enzymes. Despite its efficacy, paclitaxel has severe side effects. Herbal medicines are commonly used to treat the side effects of chemotherapy. They can be administered before, during, and after chemotherapy. Xiang-Sha-Liu-Jun-Zi Tang (XSLJZT) is a herbal formula commonly used in breast cancer patients. The main purpose of this study was to assess the pharmacokinetic (PK) influence of XSLJZT on paclitaxel PK parameters, determine its effect on CYP-450 enzyme expression, and evaluate its effect on enzyme activity. Sprague Dawley rats were classified into pretreatment and co-treatment groups, where XSLJZT was pre-administered for 3, 5, and 7 days and co-administered 2 h before paclitaxel administration. The rat liver tissues and HepG2 cells were used to determine the effects of XSLJZT on CYP3A4 enzymes. Western blot analysis was used to detect changes in CYP3A4 enzyme expression. The influence of XSLJZT on enzyme activity was evaluated using human liver microsomes, and a liquid chromatography-tandem mass spectrometric system was developed to monitor paclitaxel levels in rat plasma. Results demonstrated that XSLJZT increased the area under the concentration versus time curve (AUC) for paclitaxel in pretreatment groups by 2-, 3- and 4-fold after 3, 5, and 7 days, respectively. In contrast, no significant change in the AUC was observed in the co-treatment group. However, the half-life was prolonged in all groups from 17.11 min to a maximum of 37.56 min. XSLJZT inhibited CYP3A4 expression in both rat liver tissues and HepG2 cells in a time-dependent manner, with the highest inhibition observed after 7 days of pretreatment in rat liver tissues and after 24 h in HepG2 cells. In the enzyme kinetics study, XSLJZT inhibited enzyme activity in a competitive dose-dependent manner. In conclusion, there is a potential interaction between XSLJZT and paclitaxel at different co-treatment and pretreatment time points.